Polyphasic characterization of Aerosakkonema funiforme, Cephalothrix komarekiana, and the novel species Cephalothrix magna sp. nov. (Aerosakkonematales, Aerosakkonemataceae) from Malaysian freshwater ecosystems - Ong, Yin Sing; Teng, Sing Tung; Hii, Kieng Soon; Leaw, Chui Pin; Lim, Po Teen (Phytotaxa, 2026)
This study dealt with the taxonomy of filamentous cyanobacteria from Kota Samarahan, Sarawak, Malaysia Borneo, by employing polyphasic approach. Seven strains were successfully isolated, and their morphology was examined microscopically, and their phylogenetic relationships were inferred using the 16S rRNA gene and 16S–23S rRNA internal transcribed spacer (ITS) secondary structural information. The results revealed three species belonging to Aerosakkonemataceae, namely Aerosakkonema funiforme, Cephalothrix komarekiana, and a novel morphotype of Cephalothrix. The cell size of this undescribed morphotype was significantly larger than the known species of Cephalothrix. In the 16S rRNA gene and 16S–23S rRNA ITS phylogenetic trees, this morphotype formed a monophyletic clade with high bootstrap supports. Structural comparison of the 16S–23S rRNA ITS secondary structure showed compensatory base changes and single nucleotide polymorphisms between the new morphotype and the described species, C. komarekiana and C. lacustris. Based on the morphology and molecular characterization, we here propose Cephalothrix magna sp. nov., with the species epithet proposed under the International Code of Nomenclature (ICN) for Algae, Fungi, and Plants.